Chinese Sci-Tech Journal Databases - Linda R. Musser; Yurong Y. Atwill (Issues in Science and Technology Librarianship, 2022)
Western indexing tools have a documented English-language bias, which contributes to the challenges facing researchers publishing in their native language. There are actions that librarians can take to mitigate this bias such as including information on library guides about indexes that highlight resources not covered by traditional sci-tech indexing tools. This article introduces three academic journal databases from China that are available for North American and other institutions. With a focus on sci-tech journals, basic descriptions of coverage and functionality of these resources is presented. Significant quantities of Chinese sci-tech information are not indexed by Western sci-tech abstract and indexing tools but are available via the databases discussed.